Home Visit Process for Colorectal Cancer Patients After Ostomy Surgery : The Role of Community Nurse Practitioners - Rakguson , Rapeepat; Thanapiyawat, Natrampaporn; Komutklang , Marisa (Health Science Journal of Nakhon Ratchasima College, 2025)
Home visits play a crucial role in the care of colorectal cancer patients after ostomy surgery, particularly in community settings where patients face physical and psychological challenges. This article aims to describe the home visit process for these patients, emphasizing the role of community nurse practitioners in providing continuous care. Nurses play a vital role in educating patients about ostomy care, preventing complications, providing psychological support, and enhancing patients' quality of life. Additionally, home visits allow for assessing patients' living environments and providing personalized recommendations tailored to their specific contexts. An effective home visit process helps boost patients' and families' confidence in self-care, reduces complications, and ultimately improves the overall quality of life for colorectal cancer patients after ostomy surgery.